Competitiveness Analysis of the Productive Business Unit Catur Paramita Kintamani Coffee in Catur Village, Kintamani District, Bangli Regency - Putu Fajar Kartika Lestari; I Made Tamba; Ni Komang Winda Surya Putri (SEAS (Sustainable Environment Agricultural Science), 2024)
Kintamani coffee is grown at an altitude of 900-1000 meters above sea level near Mount Batur. As already discussed, the taste and aroma of Kintamani Coffee tends to taste citrusy. One reason is the reporting process which is unique and unusual. The purpose of the study entitled Analysis of Arabica Coffee Competitiveness in UUP (Productive Business Unit) Catur Paramitha in Catur Village, Kec. Kintamani Regency Bangli is to analyze the competitive advantage of Arabica coffee in the UUP (Productive Unit) Catur Paramitha in Catur Village, Kec. Kintamani Regency Bangli, and to analyze the comparative advantage of Arabica coffee in UUP (Productive Business Unit) Catur Paramitha in Catur Village, Kec. Kintamani Regency Bangli. This research was conducted from October to December 2022. The research location was determined using a purposive method, while the sample of respondents was determined using a purposive sampling technique with 15 respondents. The analytical method in this study uses the Policy Analysis Matrix (PAM) or government policy analysis. The results of the PAM analysis research show that Arabica Coffee farming produced by Arabica Coffee farmers in Catur Village, Kintamani District, Bangli Regency has very strong competitiveness because it is seen from the value of the Private Cost Ratio (PCR) <1, namely 0.17 and the Domestic Resources Ratio (DCR) <1, namely 0.10, which means that Arabica coffee farming has a competitive advantage and a comparative advantage, because economic efficiency is already able to compete with Arabica coffee farming in other regions. The policies owned by the government have been able to provide effective protection (protection) for Arabica coffee farming to survive until now, this is due to the existence of policies in the form of input-output prices and subsidized assistance from the government. Keywords : Arabica Coffee, Competitiveness, Policy Analysis Matrix (PAM)